The Ethical-Formative Experience of Psychoanalysis and Dialogue with Kant - Simone Alexandre Martins Corbiniano (Universidade Federal do Rio Grande do Sul, 2013)
It is understood from Lacan that ethics cannot be reduced to the simple existence of obligations, as it is intrinsically linked to the very structure of desire itself. Ethical experience creates the possibility of a potential sublimatory rupture with what has been established and isthe motivating source of the subject's entire action, there by affirming itselfas an ethical-formative experience. The ethics of Psychoanalysis foresees what could be of benefit to the subject, with all the contradictions, gaps and problems which that can bring. This reflection is based on Lacan's: The Seminar The Ethics of Psychoanalysis (Book VII), in which the author places himself at the horizon of ethics, discussing the concepts of das Ding, Kantianmoral law and sublimation.